STRUCTURAL FEATURES OF RATS’ PAROTID SALIVARY GLANDS AFTER INTRODUCTION OF PLATIFILLINUM - Tsukanov, D.V. (World of Medicine and Biology, 2012)
Determination of basic structural changes is in-process conducted in the lobules of parotid salivary gland of rats after introduction of platifillinum. It is set, that its introduction influences on the processes of secret-extrusion. In the end-pieces seromucous cells are set, secretory granules of which on a structure were, and on a tinktorial properties - serosal. In the ductal system active carry of liquid flags were determined from a vascular rate and periductal interstitium to the lumens. The amount of plasma cells, macrofages and mast cells are insreased in an interstitium, that testifies to tension of local immune barrier.